Helical ullazine-quinoxaline-based polycyclic aromatic hydrocarbons - Richter, Marcus; Hahn, Sebastian; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2019)
Polycyclic aromatic azomethine ylides (PAMYs) are powerful building blocks in the bottom-up synthesis of internally nitrogen-containing polycyclic aromatic hydrocarbons (N-PAHs) through 1,3-cycloaddition reactions. In this work, the cycloaddition reaction of PAMYs to asymmetric ortho-quinones is presented, which, in contrast to the addition to symmetric para-quinones, facilitates subsequent condensation reactions and allows the synthesis of three helical N-PAHs with ullazine-quinoxaline (UQ-1-3) backbones. UQ-1 and UQ-2 possess two helical centers; however, single-crystal X-ray analysis together with the computational modeling of UQ-3 elucidate the formation of only the thermodynamically most stable geometry with four helical centers in a (P,P,M,M) configuration. For the series UQ-1-3, the number of redox steps is directly correlated with the number of ullazine or quinoxaline units incorporated into the targeted molecular backbones. A detailed investigation of the spectroscopic and magnetic properties of the radical cation and anion as well as the dication and dianion species by in situ EPR/UV/Vis-NIR spectroelectrochemistry is provided. The excellent optical and redox properties combined with helical geometries render them possibly applicable as chiral emitter or ambipolar charge transport material in organic electronics.
First published: 05 November 2018
Gesehen am 28.02.2019